REVIEW OF EFFECTIVENESS ON ZERO RUPIAH DOWN PAYMENT HOUSING SCHEME IN JAKARTA - Kusumasari , Lita (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
DKI Jakarta is capital city with dense population in Java, Indonesia. Jakarta is severed the worst of house owning, especially for low income households. The ownership status of self-owned house in Jakarta is 41.20% while average is 84.33% in Indonesia. To overcome backlog houses throughout Indonesia, key campaign promises of Jakarta governor-elected is zero Rupiah down-payment housing scheme. This research would like to oversee the effectiveness of Zero Rupiah Down-Payment from the readiness until implementation. The research covers rules and laws supported for this program, the analysis of system implemented, and the impact toward budgeting for DKI Jakarta. The research method is qualitative mixed methods. Primary data is collecting by interviews and forum group discussion with stakeholders. Secondary data is collected by references. The result is the program is right under laws and rules. The budget is less effective in absorption because facing challenges. DKI Jakarta is financially supported in budgeting for this program but needs more commitment for continuous implementation. The Jakarta residents think that this program is beneficial but need to socialize more.